2017
DOI: 10.1016/j.bbr.2016.10.050
|View full text |Cite
|
Sign up to set email alerts
|

A role for the mu opioid receptor in the antidepressant effects of buprenorphine

Abstract: Buprenorphine (BPN), a mixed opioid drug with high affinity for mu (MOR) and kappa (KOR) opioid receptors, has been shown to produce behavioral responses in rodents that are similar to those of antidepressant and anxiolytic drugs. Although recent studies have identified KORs as a primary mediator of BPN’s effects in rodent models of depressive-like behavior, the role of MORs in BPN’s behavioral effects has not been as well explored. The current studies investigated the role of MORs in mediating conditioned app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…In the Oprm1 A112G mouse model, BPN produced a robust effect in the AA mice but failed to diminish the anxiogenic effects of the novel environment in AG and GG mice, suggesting that altered genetic signaling at MORs mediated these behavioral differences. In agreement with this characterization, approach behavior in the NIH test was blocked by the selective MOR antagonist cyprodime and in male Oprm1 −/− mice (Robinson et al, 2016). Conversely, we showed that the prototypical benzodiazepine CDP was highly efficacious across all genotypes, demonstrating the specific ability of Oprm1 A112G SNP to attenuate the efficacy of MOR compounds.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the Oprm1 A112G mouse model, BPN produced a robust effect in the AA mice but failed to diminish the anxiogenic effects of the novel environment in AG and GG mice, suggesting that altered genetic signaling at MORs mediated these behavioral differences. In agreement with this characterization, approach behavior in the NIH test was blocked by the selective MOR antagonist cyprodime and in male Oprm1 −/− mice (Robinson et al, 2016). Conversely, we showed that the prototypical benzodiazepine CDP was highly efficacious across all genotypes, demonstrating the specific ability of Oprm1 A112G SNP to attenuate the efficacy of MOR compounds.…”
Section: Discussionsupporting
confidence: 79%
“…BPN (0.25 and 0.5 mg/kg) reduced the latency to consume palatable food in the NIH test 24 h post treatment in WT female C57BL/6J mice. It is proposed that blockade of MOR mediates this anxiolytic action, as MOR agonism is prevented by this dose of BPN 24 h post treatment (Robinson et al, 2016). In the Oprm1 A112G mouse model, BPN produced a robust effect in the AA mice but failed to diminish the anxiogenic effects of the novel environment in AG and GG mice, suggesting that altered genetic signaling at MORs mediated these behavioral differences.…”
Section: Discussionmentioning
confidence: 99%
“…The buprenorphine antidepressant activity in the forced swim test in mice is absent in OPRK1 (the gene encoding KOR) gene null mutants [53]. However, in the novelty-induced hypophagia test in mice, the antidepressant effects of buprenorphine were absent in OPRM1 null mutants but retained in OPRK1 null mutants [56]. Thus, the buprenorphine MOR and KOR activities may both be relevant to its effects on rodent models of anxiety and depression.…”
Section: Expansion Of Buprenorphine For Treatment Of Mood and Anxietymentioning
confidence: 99%
“…That this activity was mediated through blockade of MOP receptors was confirmed by use of a selective MOP receptor antagonist, cyprodime. These authors suggest that antagonism of MOP receptors by buprenorphine could block stress-induced activation of MOP receptors in the VTA which has been shown to reduce dopaminergic transmission in the nucleus accumbens [63]. It would therefore appear that both KOP receptor antagonism and MOP receptor antagonism may be important for buprenorphine's ability to regulate emotional state.…”
Section: Mixed Kop/mop Antagonists Are Antidepressant In Animal Modelsmentioning
confidence: 96%
“…Initially it was believed that buprenorphine's efficacy in treating depressed patients was derived from its partial MOP agonist actions but this has been challenged in recent years with evidence suggesting these behavioural effects of buprenorphine can be attributed to its KOP receptor antagonism [58,69]. Intriguingly, the most recent data indicate that MOP receptors do play a role in buprenorphine's behavioural response where there is a motivational component [63,71] but perhaps not in the way initially envisaged. In the novelty-induced hypophagia task in C57BL/6J mice buprenorphine, when used at a time point when it was acting as an MOP receptor antagonist, reduced the latency to approach the food in the novel cage but not in MOP receptor knockout mice.…”
Section: Mixed Kop/mop Antagonists Are Antidepressant In Animal Modelsmentioning
confidence: 97%